Antibacterial Activity of Pegagan (Centella asiatica) Extract Against Bacteria Causing Postpartum Wound Infections - Gunawan, Indriani Febrishaummy; Aprilianti, Tania (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Postpartum perineal wounds are highly susceptible to bacterial infection, particularly by Staphylococcus aureus and Pseudomonas aeruginosa. Although Centella asiatica is widely recognized for its wound-healing properties, quantitative data on its antibacterial potency against postpartum-related pathogens remain limited. This study aimed to evaluate the antibacterial activity of ethanol extract of C. asiatica against S. aureus and P. aeruginosa by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Fresh leaves of C. asiatica were extracted using 96% ethanol. Ethanol was selected as the extraction solvent due to its ability to dissolve both polar and semi-polar bioactive compounds, including flavonoids, tannins, and triterpenoids, which are associated with antibacterial activity. Phytochemical screening confirmed the presence of flavonoids, tannins, saponins, alkaloids, and triterpenoids. Antibacterial activity was assessed using the broth microdilution method. The extract exhibited concentration-dependent inhibition, with MIC values of 12.5% against S. aureus and 3.12% against P. aeruginosa, while bactericidal activity for both strains was observed at 25%. These findings provide quantitative evidence of the antibacterial potential of C. asiaticaethanol extract against key bacteria associated with postpartum wound infections, highlighting its potential as a natural antibacterial agent for postpartum wound management.